IL-27 Regulated CD4+IL-10+ T Cells in Experimental Sjögren Syndrome - Qi, Jingjing; Zhang, Zhuoya; Tang, Xiaojun; Li, Wenchao; Chen, Weiwei; Yao, Genhong (Frontiers in Immunology, 2020)
Interleukin 27 (IL-27) plays diverse immune regulatory roles in autoimmune disorders and promotes the generation of IL-10 producing CD4+ T cells characterized by producing the immunosuppressive cytokine IL-10. However, whether IL-27 participates in pathological progress of Sjögren’s syndrome (SS) through regulating CD4+IL-10+ T cells remains unknown. Here we aimed to explore the potential role of IL-27 and CD4+IL-10+ T cells in the pathogenesis of SS. The IL-27 gene knockout non-obese diabetic (Il-27-/-NOD) mice were generated and injected with exogenous IL-27. Exogenous injection of IL-27 and neutralization of IL-27 with anti-IL27 antibody in NOD mice were performed. The histopathological changes in submandibular glands, lacrimal glands and lung, salivary flow rate and percentages of CD4+IL-10+ T cells were determined. And, ovalbumin (OVA) immunized C57L/B6 mice were injected with IL-27 to detect the percentage of CD4+IL-10+ T cells. In vitro, splenic naïve T cells from C57L/B6 mice were cultured with IL-27 for 4 days to induce the differentiation of CD4+IL-10+ T cells. In addition, IL-27, IL-10 and CD4+IL-10+ T cells were determined in health control (HC) and SS patients. The results showed that Il-27-/-NOD mice had more severe disease and lower level of CD4+IL-10+ T cells than control mice. And IL-27 promoted the generation and differentiation of CD4+IL-10+ T cells in vivo and in vitro significantly. In agree with the findings in the SS-like mice, patients with SS showed lower levels of IL-27, IL-10 and CD4+IL-10+ T cells. Our findings indicated that IL-27 deficiency aggravated SS by regulating CD4+IL-10+ T cells. Targeting IL-27 and CD4+IL-10+ T cells may be a novel therapy for patients with SS.